Upaya Peningkatan Kualitas Layanan Referensi dalam Memenuhi Kebutuhan Pemustaka di Perpustakaan Universitas Sumatera Utara - Nurul Ummi; Retno Sayekti; Muslih Faturrahman (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2024)
The aim of this research is to determine efforts to improve the quality of reference services to library users. So the attitude of users in the library is very important to know the needs and desires of users and to know user satisfaction. Therefore, information regarding user satisfaction can be used as criticism and input for service strategies. The results of this research show that efforts to improve the quality of reference services in meeting the needs of librarians are carried out in 2 ways, namely: with general efforts by means of smiles, greetings, greetings, politeness and politeness, and special efforts such as from the librarian's personal abilities. in serving readers, such as frequently carrying out promotional activities, both through literacy class activities and promotions on various media such as Instagram, Facebook and YouTube. The obstacles faced by librarians in improving the quality of reference services in meeting library needs, such as the available e-book databases, are not evenly distributed across all study programs. The e-journal database that is subscribed to does not fully contain the core journals for each study program. There is still a lack of user understanding about the differences between reference books and standard books, where reference books are a type of book that cannot be borrowed. There is an inappropriate attitude of some users and a lack of skills that users have regarding online-based reference services.